The effects of tryptophan supplementation on stress and aggression in Nile tilapia - Meletti Vieira, Bruna Renata [UNESP] (2021)
Nile tilapia farmers must deal with production challenges, such as increased aggressiveness and high stress levels, which potentially diminishes fish welfare. Tryptophan supplementation is a strategy to cope with such problems. However, data is scarce on how tryptophan affects the aggressiveness of this species and other aspects need to be understood on how it influences stress in fish. In this study, we investigate how a 1x (0.32%), 4x (1.28%) and 8x (2.56%) supplemented tryptophan diet affects aggressiveness and stress in Nile tilapia. Aggressiveness in fish was assessed after short-term exposure (7 days) to a tryptophan supplemented diet while stress in fish was assessed after long-term exposure (60 days). The 4x and 8x diets reduced aggressiveness in fish, while the 8x diet reduced aggressiveness more effectively than the 4x diet. Also, long-term exposure to the 8x diet reduced stress in fish, before and after they were exposed to an acute stress. In conclusion, this study showed that a tryptophan supplemented diet can diminish aggressiveness and stress in Nile tilapia, thus demonstrating a potential to improve fish welfare.